Chronic Insomnia - Buysse, Daniel J. (2008)
Ms. F, a 42-year-old divorced woman, presents for evaluation of chronic insomnia. She complains of difficulty falling asleep, often 30 minutes or longer, and difficulty maintaining sleep during the night, with frequent awakenings that often last 30 minutes or longer. These symptoms occur nearly every night, with only one or two “good” nights per month. She typically goes to bed around 10:00 p.m. to give herself adequate time for sleep, and she gets out of bed around 7:00 a.m. on work days and as late as 9:00 a.m. on weekends. Her nighttime sleep problems result in daytime irritability and difficulty focusing and organizing her thoughts, which subjectively impair her work as an administrative assistant, although her performance evaluations have been satisfactory. She says that she has “no energy for anything extra,” that her house is a mess, and that she routinely declines invitations to join social and even family activities. Her insomnia began approximately 5 years ago during a period of increased life stress related to a difficult divorce and a job change. At that time she was diagnosed with major depression and was started on a successful trial of escitalopram, which she continues at a dose of 10 mg/day. Her current symptoms are distinct from those that were associated with her episode of major depression. She denies pervasive sadness or loss of interest, but she is very frustrated with her inability to function more effectively, which she attributes to her insomnia. In fact, she believes that her cognitive difficulties and irritability are most noticeable after nights of particularly poor sleep. Her medical history is unremarkable other than a past history of Graves’ disease. She has been treated with levothyroxine for the past 15 years. How should Ms. F be evaluated? What medical testing, if any, would be appropriate? What factors should be considered in formulating a treatment plan? What treatments would be appropriate?